Reflexões sobre as cotas e a assistência estudantil da Universidade Federal do Cariri - Dias, Juliana Moreira (2023)
As measures aimed at significantly expanding access to higher education in the country, there is the Quota Law, through Law 12,711, published in 2012, which aims to allow students to enter higher education and technical education in the federal education network, reserving half of the places for people who completed secondary or primary education entirely at a public school, as a condition of access to higher education or technical education. Thus, this dissertation has the general objective of analyzing the implications of the Law of Quotas in Student Assistance at the Federal University of Cariri (UFCA) and the specific objectives of understanding the trajectory of affirmative actions in Brazil and its implementation through the Law of Quotas and the Program Permanence Grant; know the trajectory of the inclusion of population groups made up of black, mixed race, indigenous people and people with disabilities in the Quota Law; analyze the graduation profile in federal higher education after the implementation of the quota law; and reflect on the challenges posed to student assistance after the implementation of quotas in higher education. To do so, we use the critical-dialectic method, inspired by Marx. The methodological approach used in this study was qualitative. We characterize the research as a field study, carried out at UFCA, in which the study universe refers to quota students and semi-structured directed interviews were carried out with quota students from different courses. This research is also characterized as documentary, in which institutional reports and national reports of research carried out with students from higher education and technological education students from federal institutions. The results allow us to see that the majority of UFCA quota holders belong to the Civil Engineering course, with 422 students; the L2 quota, which refers to black, brown or indigenous people with an income of up to 1.5 minimum wages, accounts for the second largest group of quota holders, with 33.8% of the total number of subjects, impacting student assistance; 50% of those interviewed joined UFCA under the L2 quota; 2.61% of the total quota holders are people with disabilities; approval of interviewees regarding UFCA; reports of difficulties during graduation, such as in specific subjects due to gaps in secondary education, financial difficulties while waiting to receive assistance from the Dean of Student Affairs, considering they are on the reserve register; low quality in public transport; lack of knowledge of the majority of interviewees about affirmative actions. It is concluded that it is necessary for the Federal University of Cariri to incorporate into its management policy the massive dissemination of the meaning of affirmative actions and, in the particularity of student assistance, to develop monitoring actions for quota students in order to contribute to improving their academic performance.